2014
DOI: 10.1055/s-0033-1359200
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of celiac disease at endoscopy

Abstract: An approach based solely on standard clinical suspicion and endoscopic findings is associated with a significant miss rate for celiac disease. A strategy to biopsy based on the derived celiac disease prediction models using easily obtained information prior to or during endoscopy, maximized the diagnosis while minimizing unnecessary biopsies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 37 publications
1
30
2
1
Order By: Relevance
“…Endoscopy with histological assessment of villous atrophy of the duodenum still represents the gold standard for diagnosis of celiac disease. However, WLE with random biopsies in the duodenum has not been shown to have great accuracy in the diagnosis of celiac disease [10,13]. Our study has shown a poorer correlation between WLE grade and Marsh histologic grade in the diagnosis of celiac disease (r = 0.31; P = 0.01) compared with the i-SCAN-HDWI endoscopic technique.…”
contrasting
confidence: 55%
See 1 more Smart Citation
“…Endoscopy with histological assessment of villous atrophy of the duodenum still represents the gold standard for diagnosis of celiac disease. However, WLE with random biopsies in the duodenum has not been shown to have great accuracy in the diagnosis of celiac disease [10,13]. Our study has shown a poorer correlation between WLE grade and Marsh histologic grade in the diagnosis of celiac disease (r = 0.31; P = 0.01) compared with the i-SCAN-HDWI endoscopic technique.…”
contrasting
confidence: 55%
“…Our study has shown a poorer correlation between WLE grade and Marsh histologic grade in the diagnosis of celiac disease (r = 0.31; P = 0.01) compared with the i-SCAN-HDWI endoscopic technique. In addition, a more recent paper by Barada et al has indicated that standard endoscopic findings were related to a significant rate of underdiagnosis of celiac disease [13]. Novel emerging endoscopic techniques such as water immersion techniques, chromoendoscopy, and optical digital enhancement virtual chromoendoscopy have been developed to better characterize in detail the vascular and surface architecture of the gastrointestinal tract.…”
mentioning
confidence: 99%
“…Our hospital laboratory reports a combined tTG IgA/IgG result. Positive tTG serology was defined as a level of 30 U/mL or above . HLA genotyping was performed using an Affymetrix Kaiser Axiom array to locate single nucleotide polymorphisms (SNPs) on chromosome 6.…”
Section: Susceptibility For Celiac Disease Based On Tissue Transglutamentioning
confidence: 99%
“…1). Although these endoscopic markers, when identified during conventional EGD, have shown good specificity (about 95-100%) for the diagnosis of CD, they are lacking in sensitivity (50-80%) [9,10,11]. However, these figures refer to endoscopic markers identified by conventional EGD.…”
Section: Diagnosis Of Suspected CDmentioning
confidence: 99%